Analisis Faktor Risiko Paparan Debu Kayu Terhadap Gangguan Fungsi Paru Pada Pekerja Industri Pengolahan Kayu PT. Surya Sindoro Sumbing Wood Industry Wonosobo - Suryani, Meta; Setiani, Onny; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2005)
ABSTRAK Background: One of the negative impacts of wood processing industry is air pollution caused by wood ash that occurred during the process or as the output of the industry. The wood ash will contaminate the industry area as well as the environment so not only the workers, but also the people living around the factory will be exposed to ash from raw material, added material, and the output, thus causing lung function disturbance.  The aim of this research is to measure the risk of factors that causes lung function disturbance to the workers in wood processing industry at PT Surya Sindoro Sumbing Wood Industry Wonosobo. Method : This is an observational research using cross-sectional design. The samples are workers that fulfill the criteria inclusively and exclusively as many as 70 persons. This research was done in February 2005 and the data collection was done using wood ash content measurement in Furniture Component (FC) and Wood Working Area (WWA) sections, lung function capacity measurement, body height and body weight measurements, as well as interview with the respondents. Result : This research showed that the amount of the wood ash in WWA and FC of 6.1452mg/m3 and 4.0101mg/m3 respectively; and the average of lung function capacity on the workers is 92.04% FEV1/FVC with standard deviation of 6.68 with the lowest and the highest rate of 66% FEV1/FVC and 100% FEV1/FVC respectively. The data analysis in this research used chi-square test, Independent   t Test,while the multivariat analysis used logistic regression test with enter method. The statistics test showed that there was a relationship between the working period and the smoking habit with lung function capacity (p<0.05),there was no significant difference of lung function between WWA workers and FC workers (p>0.05). Conclusions : The working period and the smoking habit at the same time can become the risk factor of the lung function disturbance. As such, smoking prohibition during working hours in the wood processing industry should be applied in order to avoid lung function disturbance among the workers.   Key words : wood ash, lung function disturbance, wood processing industry